Effect of surgery on oxidative stress and endogenous tocopherol concentrations in juvenile female dogs - Giovanna Lucrezia Costa; Fabio Leonardi; Patrizia Licata; Marco Tabbì; Nicola Iannelli; Diego Iannelli; Daniele Macrì; Fabio Bruno; Vincenzo Ferrantelli; Vincenzo Nava; Claudia Interlandi; Giuseppe Bruschetta (Acta Veterinaria Scandinavica, 2024)
Abstract Background Surgery such as ovariectomy causes an inflammatory and oxidative stress. This study was designed to evaluate endogenous tocopherol levels in response to surgical oxidative stress induced by abdominal surgery (ovariectomy) in thirty-two juvenile female dogs. The dogs received meloxicam before surgery (0.2 mg/kg SC) and after surgery (0.1 mg/kg OS every 24 h), 0.03 mg/kg of atropine sulfate (IM), and propofol 4 mg/kg intravenously (IV). General anesthesia was maintained with sevoflurane. Physiological, hematological and biochemical parameters, malondialdehyde (MDA) and α-, δ-, γ-tocopherols were evaluated at baseline, 36 and 48 h after surgery. Results The physiological parameters remained within normal ranges. Blood glucose concentration increased, while the albumin levels decreased after surgery. Rescue analgesia was not required. MDA levels increased above the baseline at 36 and 48 h after surgery (P < 0.001). The α-, δ-, and γ-tocopherol concentrations decreased from baseline at 36 and 48 h after surgery (P < 0.001). Conclusions Surgery in juvenile female dogs revealed oxidative, increased MDA concentrations, reduced tocopherol levels, and had a clinically insignificant influence on homeostasis.